PEMANFAATAN PATI JAGUNG TERMODIFIKASI TEKNIK MICROWAVE PADA MIE JAGUNG - Rasyid, Nur Pratiwi; Zainuddin, Asniwati (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2018)
Modification of corn starch had been conducted with HMT (Heat MoistureTreatment) techniques, modification starch with acid, or by usingenzymes. However, in this research modification corn starch was usingmicrowave techniques with an energy 28.80 kJ. The purpose of this studywas to determine the effect of modification corn starch on making cornnoodles and to know the acceptance of panelists on corn noodles treatedwith microwave and non-microwave. The results obtained the treatmentcorn noodles from non-microwave flour showed a higher amount of waterand protein content compared to the treatment of corn noodles frommicrowave flour, while the treatment of corn noodles from microwavedflour obtained a decrease in moisture, fat, ash content and carbohydrates.The results of organoleptic testing of hedonic 1-5 scale on corn noodleswith microwave treatment were acceptable for all treatments both fromcolor (4.08), flavor (4.03), taste (3.1) and texture (3.58).Keywords : Microwave, Corn Noodles, Organoleptic Testing, Modification Starch.